Lithium secondary battery having high specific capacity

By controlling the distribution of sulfur-based compounds and using sulfur-carbon composite materials, the problem of low specific capacity of lithium-sulfur batteries is solved, and a lithium-sulfur battery with high specific capacity and energy density is achieved, which improves the charging and discharging efficiency and life of the battery.

CN119278526APending Publication Date: 2025-01-07LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380043495.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-03
Filing Date
2023-10-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The specific capacity of existing lithium-sulfur batteries is much lower than the theoretical value, mainly because the dissolution of lithium polysulfide in the positive electrode in the electrolyte causes side reactions and charge and discharge efficiency to decrease.

Method used

By controlling the content ratio (RSL) of the sulfur in the electrolyte is below 15%, it ensures that the content of sulfur-based compounds in the positive electrode is high and the dissolution of sulfur is reduced. A sulfur-carbon composite is used as the positive electrode material and contains it in the electrolyte solution. Inorganic sulfur and lithium polysulfide, optimize the electrolyte composition to improve the specific capacity and energy density of lithium-sulfur batteries.

Benefits of technology

The specific capacity of lithium-sulfur battery reaches more than 1,000mAh/g and the energy density reaches more than 300Wh/kg, significantly improving the charging and discharging efficiency and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present disclosure relates to a lithium-sulfur battery having high capacity and high energy density, and provides new parameters for the characteristics of the lithium-sulfur battery having high capacity and high energy density. A lithium-sulfur battery according to the present disclosure includes a positive electrode including a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution, wherein the content ratio (RSL) of sulfur (S) according to Formula 1 as defined herein is 15% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a lithium secondary battery, and more particularly, to a lithium-sulfur battery having a high specific capacity.

[0002] This application claims priority to Korean Patent Application No. 10-2023-0057999 filed in Korea on May 3, 2023, and Korean Patent Application No. 10-2023-0133558 filed in Korea on October 6, 2023, the disclosures of which are incorporated herein by reference in their entirety. Background Art

[0003] As the application range of lithium secondary batteries expands not only to mobile electronic devices but also to electric vehicles (EVs) and energy storage systems (ESSs), there is an increasing demand for lithium secondary batteries having high capacity, high energy density, and long lifespan.

[0004] Among various types of lithium secondary batteries, lithium-sulfur batteries are battery systems that use a sulfur-based material containing a sulfur-sulfur (SS) bond as a positive electrode active material and use lithium metal, a carbon-based material capable of inserting / deinserting lithium ions, or silicon and tin capable of alloying with lithium as a negative electrode active material.

[0005] In lithium-sulfur batteries, sulfur, which is the main material of the positive electrode active material, has a low atomic weight, is very abundant in nature and can be found all over the world, is low in cost, and is non-toxic and environmentally friendly.

[0006] In addition, through the conversion reaction of lithium ions and sulfur at the positive electrode (S 8 +16Li + +16e - -> 8Li 2 S), lithium-sulfur batteries have a theoretical specific capacity of 1,675mAh / g, and when lithium metal is used for the negative electrode, the theoretical energy density is 2,600Wh / kg. This value is much higher than other battery systems currently being studied (Ni-MH battery: 450Wh / kg; Li-FeS battery: 480Wh / kg; Li-MnO 2 Since the theoretical energy density of lithium-sulfur batteries is 1,000Wh / kg (1,000Wh / kg for lithium-ion batteries and 800Wh / kg for Na-S batteries) and 250Wh / kg for lithium-ion batteries, lithium-sulfur batteries have attracted much attention as high-capacity, environmentally friendly and low-cost lithium secondary batteries among the secondary batteries developed so far.

[0007] During discharge, sulfur in a lithium-sulfur battery undergoes a reduction reaction at the positive electrode by accepting electrons, and in this case, lithium polysulfide (Li 2 S x, x = 1 to 8), and part of the lithium polysulfide is easily dissolved in the electrolyte, causing side reactions in the battery and faster degradation of the battery, and a shuttle reaction occurs during charging, resulting in a significant decrease in charge and discharge efficiency. For this reason, the specific capacity of lithium-sulfur batteries developed so far is much lower than the theoretical specific capacity.

[0008] Therefore, it is necessary to develop lithium-sulfur batteries with a specific capacity as high as the theoretical specific capacity. Summary of the invention

[0009] Technical issues

[0010] The present disclosure is designed to solve the above-mentioned problems, and thus the present disclosure is directed to providing a lithium-sulfur battery having a specific capacity as high as a theoretical specific capacity.

[0011] The present disclosure further relates to providing a lithium-sulfur battery with high energy density.

[0012] Technical Solution

[0013] In order to achieve the above objectives, according to one aspect of the present disclosure, a lithium-sulfur battery according to the following embodiments is provided.

[0014] The lithium-sulfur battery according to the first embodiment includes a positive electrode including a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the content ratio (R SL ) is less than 15%:

[0015] [Formula 1]

[0016] R SL (%) = W SE / W SP × 100

[0017] Wherein W SE is the weight of sulfur (S) in the sulfur-based compound present in the electrolyte, and the W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0018] According to the second embodiment, in the first embodiment, W in Formula 1 is SE and W SP Each may represent a value measured in a discharge state of 1.7V to 1.9V.

[0019] According to a third embodiment, in the first or second embodiment, the sulfur-based compound present in the electrolyte may include inorganic sulfur (S 8 ), lithium polysulfide (Li 2 S x, 1≤x≤8) or a mixture thereof.

[0020] According to a fourth embodiment, in any one of the first to third embodiments, the sulfur-based compound present in the positive electrode may include inorganic sulfur (S 8 ).

[0021] According to a fifth embodiment, in any one of the first to fourth embodiments, based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery, the W SE It may be 15% by weight or less.

[0022] According to a sixth embodiment, in any one of the first to fifth embodiments, based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery, the W SP It may be 65% by weight or more.

[0023] According to a seventh embodiment, in any one of the first to sixth embodiments, based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery, the W SP It may be 75.5% by weight or more.

[0024] According to an eighth embodiment, in any one of the first to seventh embodiments, the lithium-sulfur battery may satisfy the following Formula 2:

[0025] [Formula 2]

[0026] W' SP > 1.2 × W' SE +56.86

[0027] Wherein W' SE is the weight % of sulfur (S) in the sulfur-based compounds present in the electrolyte based on the total weight of sulfur (S) in the sulfur-based compounds contained in the lithium-sulfur battery, and W' SP It is the weight % of sulfur (S) in the sulfur-based compound present in the positive electrode based on the total weight of sulfur (S) in the sulfur-based compound contained in the lithium-sulfur battery.

[0028] According to a ninth embodiment, in any one of the first to eighth embodiments, the lithium-sulfur battery may satisfy the following Formula 3:

[0029] [Formula 3]

[0030] 10.667 × R S / C - 10.633 > R SL

[0031] Wherein R SLis the content ratio of sulfur (S) according to Formula 1, and the R S / C is the weight ratio of sulfur (S) to carbon (C) in the sulfur-carbon composite.

[0032] According to a tenth embodiment, in any one of the first to ninth embodiments, the sulfur-carbon composite may have a sulfur / carbon weight ratio (S / C weight ratio) of 2.5 g / g or less.

[0033] According to an eleventh embodiment, in any one of the first to tenth embodiments, the positive electrode may include a current collector and a positive electrode active material layer including the sulfur-carbon composite, and the weight of the sulfur-carbon composite may be 80 wt % or more based on the total weight of the positive electrode active material layer.

[0034] According to a twelfth embodiment, in any one of the first to eleventh embodiments, a weight ratio of the electrolytic solution to sulfur in the sulfur-carbon composite (E1 / S weight ratio) may be 3.5 g / g or less.

[0035] According to a thirteenth embodiment, in any one of the first to twelfth embodiments, the electrolyte may include a non-cyclic ether, a cyclic ether, or a mixture thereof.

[0036] According to a fourteenth embodiment, in any one of the first to thirteenth embodiments, the electrolyte may include a mixture of the non-cyclic ether and the cyclic ether, and a volume ratio of the non-cyclic ether to the cyclic ether may be 5:95 to 95:5 (volume / volume).

[0037] According to a fifteenth embodiment, in any one of the first to fourteenth embodiments, the specific capacity of the lithium-sulfur battery may be 60% or more of a theoretical specific capacity calculated from the total amount of the sulfur-based compound contained in the lithium-sulfur battery.

[0038] According to a sixteenth embodiment, in any one of the first to fifteenth embodiments, the sulfur-based compound may include inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1≤x≤8) or a mixture thereof.

[0039] According to a seventeenth embodiment, in any one of the first to sixteenth embodiments, the lithium-sulfur battery may have a specific capacity of 1,000 mAh / g or more.

[0040] According to an eighteenth embodiment, in any one of the first to seventeenth embodiments, the lithium-sulfur battery may have an energy density of 300 Wh / kg or more.

[0041] According to a nineteenth embodiment, in any one of the first to eighteenth embodiments, the lithium-sulfur battery may be a coin-type battery, a pouch-type battery, or a cylindrical battery.

[0042] According to another aspect of the present disclosure, there is a method of evaluating specific capacity of a lithium-sulfur battery according to the following embodiment.

[0043] The method for evaluating the specific capacity of a lithium-sulfur battery according to the twentieth embodiment is a method for evaluating the specific capacity of a lithium-sulfur battery comprising a positive electrode including a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode or the electrolyte comprises a sulfur-based compound, and the evaluation method comprises: SL ) is a lithium-sulfur battery with a capacity below 15% and is determined to be a high specific capacity battery:

[0044] [Formula 1]

[0045] R SL (%) = W SE / W SP × 100

[0046] Wherein W SE is the weight of sulfur (S) in the sulfur-based compound present in the electrolyte, and the W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0047] According to a twenty-first embodiment, in the twentieth embodiment, the high specific capacity battery may have a specific capacity of 1,000 mAh / g or more.

[0048] Beneficial Effects

[0049] According to one aspect, the lithium-sulfur battery of the present disclosure may have a specific capacity as high as the theoretical specific capacity.

[0050] In particular, the lithium-sulfur battery of the present disclosure may have a specific capacity of 1,000 mAh / g or more.

[0051] According to one aspect, the lithium-sulfur battery of the present disclosure may have a high energy density.

[0052] In particular, the lithium-sulfur battery of the present disclosure may have an energy density of 300 Wh / kg or more. DETAILED DESCRIPTION

[0053] Hereinafter, the present disclosure will be described in more detail.

[0054] It should be understood that, as used in this specification, "comprising", "including" or "having" specify the presence of the stated element and do not preclude the presence or addition of one or more other elements unless expressly stated otherwise.

[0055] The terms "about" or "approximately" as used herein are used in the sense of being equal to or close to when given the manufacturing and material tolerances inherent in the stated circumstances, and are used to prevent unscrupulous infringers from unfairly taking advantage of this disclosure in which exact or absolute numbers are stated to assist in understanding the disclosure.

[0056] Throughout the specification, "A and / or B" means A or B or both.

[0057] As used herein, the term "composite" refers to a material having physically and chemically distinct phases and more efficient functions, which is formed by combining two or more materials.

[0058] As used herein, the term "(poly)sulfide" encompasses the concepts of "(poly)sulfide ion (S x 2- , 1 ≤ x ≤ 8)" and "(poly)sulfide lithium (Li 2 S x or Li 2 S x - , 1 ≤ x ≤ 8)".

[0059] As used herein, the term "polysulfide" encompasses the concepts of "polysulfide ion (S x 2- , 1 < x ≤ 8)" and "polysulfide lithium (Li 2 S x or Li 2 S x - , 1 < x ≤ 8)".

[0060] Unless otherwise specified, the unit "mAh / g s " as used herein represents the capacity of sulfur (S) per unit weight and can be used together with other expressions such as mAh / g(s), mAh / gs.

[0061] Unless otherwise specified, the unit "mg s / cm 2 " as used herein represents the weight of sulfur (S) per unit area and can be used together with other expressions such as mg(s) / cm 2 , mAh / gs.

[0062] Due to sulfur (S 8) is reduced and the lithium polysulfide produced by the reduction reaction dissolves from the positive electrode into the electrolyte, and the lithium-sulfur battery exhibits a battery capacity lower than the theoretical capacity.

[0063] According to one aspect of the present disclosure, a lithium-sulfur battery having high capacity, particularly high specific capacity, is provided.

[0064] A lithium-sulfur battery according to one aspect of the present disclosure contains a positive electrode including a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0065] In one embodiment of the present disclosure, specifically, the lithium-sulfur battery may include an electrode assembly, the electrode assembly containing the positive electrode including the sulfur-carbon composite, the negative electrode, and a separator interposed between the positive electrode and the negative electrode; an electrolyte; and a shell accommodating the electrode assembly.

[0066] In this case, in the lithium-sulfur battery, the weight ratio R of sulfur (S) according to the following formula 1: SL It is below 15%.

[0067] [Formula 1]

[0068] R SL (%) = W SE / W SP × 100

[0069] Where W SE is the weight of sulfur (S) in the sulfur-based compounds present in the electrolyte, and

[0070] W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0071] As mentioned above, the lithium-sulfur battery comprises inorganic sulfur (S 8 ) as the positive electrode active material. In the lithium-sulfur battery, lithium (poly) sulfide is generated by a reduction reaction at the positive electrode during discharge. When the generated lithium (poly) sulfide is dissolved by the electrolyte and eluted from the positive electrode into the electrolyte, the amount of lithium (poly) sulfide oxidized at the positive electrode during charging of the lithium-sulfur battery becomes less, resulting in a decrease in the capacity of the lithium-sulfur battery.

[0072] The inventors of the present disclosure have found that having an R of less than 15% SL The lithium-sulfur battery is able to achieve high capacity. In other words, there is an advantageous effect of achieving high capacity when the active material present in the electrolyte is maintained below a certain level compared to the active material present in the positive electrode of the lithium-sulfur battery. To quantify this effect, R SLIt is newly defined as the ratio of the weight of sulfur (S) in the sulfur-based compound present in the electrolyte to the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0073] Regarding this mechanism, any sulfur (S)-containing material derived from the positive electrode active material of a lithium-sulfur battery is collectively referred to as a "sulfur-based compound". The sulfur-based compound may include, for example, inorganic sulfur (S 8 ) or lithium sulfide (Li 2 S) formed by the oxidation reaction, more specifically, inorganic sulfur (S 8 ), lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 1<x≤8), disulfide, carbon-sulfur polymer ((C 2 S y ) n , y = 2.5 to 50, n ≥ 2) or two or more thereof.

[0074] In one embodiment of the present disclosure, for ease of description, lithium sulfide (Li 2 S) in lithium (poly)sulfide (Li 2 S x , x=1), and in this case, the lithium (poly)sulfide can be represented by the chemical formula Li 2 S x = , wherein 1≤x≤8. Therefore, in one embodiment of the present disclosure, the sulfur-based compound may include, for example, inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1≤x≤8) or two or more thereof.

[0075] According to one aspect of the present disclosure, a ratio of the amount of sulfur (S) present in an electrolyte to the amount of sulfur (S) present in a positive electrode of a lithium-sulfur battery having a high specific capacity is newly proposed.

[0076] Specifically, according to one aspect of the present disclosure, a lithium-sulfur battery is provided, wherein the weight ratio of sulfur (S) according to the above formula 1 is R SL It is below 15%.

[0077] R SL represents the ratio (percentage (%)) of the weight of sulfur (S) in the sulfur-based compound present in the electrolyte of the lithium-sulfur battery to the weight of sulfur (S) in the sulfur-based compound present in the positive electrode. Specifically, by dividing R according to the following formula 1 SL Controlled below 15%, a lithium-sulfur battery with high capacity is provided.

[0078] [Formula 1]

[0079] R SL (%) = W SE / W SP × 100

[0080] Where W SE is the weight of sulfur (S) in the sulfur-based compounds present in the electrolyte, and

[0081] W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0082] In one embodiment of the present disclosure, the lithium-sulfur battery having a high specific capacity may have an R of 15% or less. SL , regardless of whether the lithium-sulfur battery is charged or discharged. Preferably, it is necessary to control the rate of sulfur loss from the positive electrode caused by the dissolution of lithium (poly)sulfide generated at the positive electrode into the electrolyte during the discharge of the lithium-sulfur battery, and when the lithium-sulfur battery is discharged, R SL It can be less than 15%.

[0083] In another embodiment of the present disclosure, the R of the lithium-sulfur battery having a high specific capacity SL It can be 14% or less, 13% or less, or 12% or less. SL The smaller the R is, the higher the capacity of the lithium-sulfur battery can be, so the lower limit is not limited to a specific range. For example, within the range satisfying the above range, R SL It can represent a value of 0.5% or more, 1% or more, 3% or more, 5% or more, 7% or more, or 10% or more. In another example, R SL It may be 0.5% to 15%, 1% to 14%, 2% to 13%, 3% to 12%, 4% to 12.5%, or 5% to 12%, but the disclosure is not limited thereto.

[0084] In the following, the measurement of R is described SL method.

[0085] In one embodiment of the present disclosure, when the lithium-sulfur battery is discharged to 1.7V to 1.9V, for example, 1.8V, R SL .

[0086] Specifically, after disassembling a lithium-sulfur battery that has been discharged to, for example, 1.7 V to 1.9 V, specifically 1.8 V, R can be measured by the ratio of the weight of sulfur (S) derived from the sulfur-based compound present in the electrolyte to the weight of sulfur (S) derived from the sulfur-based compound present in the positive electrode. SL .

[0087] In the above formula 1, the weight of sulfur (S) in the sulfur-based compound present in the electrolyte is "W SE ", and the weight of sulfur (S) in the sulfur-based compound present in the positive electrode is "W SP ”.

[0088] In one embodiment of the present disclosure, as described above, W SE and W SP Each can be measured after disassembling a lithium-sulfur battery that has been discharged to, for example, 1.7V to 1.9V, in particular 1.8V.

[0089] In one embodiment of the present disclosure, the sulfur-based compound present in the electrolyte of the lithium-sulfur battery may be derived from a material dissolved from the positive electrode during operation of the lithium-sulfur battery, and the sulfur-based compound may include, for example, inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1<x≤8) or a mixture thereof. Preferably, the sulfur compound present in the electrolyte is a material that can be dissolved by the electrolyte of the lithium-sulfur battery, and may include lithium polysulfide (Li 2 S x , 1<x≤8).

[0090] In one embodiment of the present disclosure, W SE It can be inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1≤x≤8) or the total weight of a mixture thereof. Preferably, W SE It can be lithium polysulfide (Li 2 S x , 1<x≤8). More preferably, W SE It can be lithium polysulfide (Li 2 S x , 2<x≤8), more preferably lithium polysulfide (Li 2 S x , the total weight of 3≤x≤4).

[0091] W SE The measurement may be performed by a known method or a newly developed method of measuring the content of sulfur (S) in a sulfur-based compound dissolved in the electrolyte of the lithium-sulfur battery, and the measurement method is not limited to a specific method.

[0092] According to one embodiment of the present disclosure, W can be measured by the following method SE .

[0093] First, the lithium-sulfur battery to be measured is disassembled to separate the positive electrode / diaphragm / negative electrode, and the separated positive electrode / diaphragm / negative electrode is each placed in a container filled with a specified mass of solvent to extract the sulfur compound. In this case, the extraction of the sulfur compound can be preferably performed for more than 20 minutes, specifically 20 minutes. After the extraction, it can be stored in a glove box. Therefore, the extraction solvents of the positive electrode, the diaphragm and the negative electrode can be stored separately or in combination, and are preferably stored separately. The remaining positive electrode, the diaphragm and the negative electrode are stored in the glove box. The glove box can be filled with an inert gas, such as nitrogen or argon.

[0094] In one embodiment of the present disclosure, the derivatization reagent may be added to dimethoxyethane and vortexed and the extract of each electrode may be added and then vortexed before analyzing the extraction solvent, for example, using HPLC. 2 S 3~4 ) and / or long-chain LiPS(Me 2 S 5~8 ) exists. The data analyzed by HPLC were divided into derivatized LiPS and inorganic sulfur (S 8 ), and quantitative analysis was performed using a calibration curve with each concentration of standard short-chain LiPS and inorganic sulfur. In the case of the long-chain LiPS, the concentration of the storage solution was calculated using the dilution ratio by quantitatively analyzing the sample obtained by fractionation.

[0095] In this case, an extraction solvent suitable for each sulfur compound to be extracted can be used, or a solvent having the same composition as the non-aqueous solvent in the electrolyte can be used. When the extraction is completed, each solvent is obtained and analyzed to measure the amount of sulfur compounds present in the electrolyte, and the weight of sulfur (S) in the electrolyte is calculated using their sum.

[0096] As described below, in this case, after the extraction, the positive electrode can be dried at room temperature for more than 1 hour, for example 1 hour, and scraped from the current collector, and then the weight of sulfur present in the positive electrode (W) can be calculated by elemental analysis. SP ).

[0097] The method of extracting the sulfur-based compound from the separated electrolyte solution may use, for example, liquid chromatography, but the extraction means is not limited thereto.

[0098] In one embodiment of the present disclosure, the sulfur-based compound present in the positive electrode of the lithium-sulfur battery may be an input material when manufacturing the lithium-sulfur battery or a material formed by oxidation and reduction reactions during operation of the lithium-sulfur battery. In particular, the sulfur-based compound may include inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1≤x≤8) or a mixture thereof.

[0099] Specifically, as explained below, due to W SP The sulfur-based compound present in the positive electrode may include the sulfur-based compound present in the positive electrode in the discharged state of the lithium-sulfur battery. Specifically, the sulfur-based compound present in the positive electrode may include lithium (poly) sulfide (Li 2 S x , 1≤x≤8), specifically lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 1<x<3) or a mixture thereof. More specifically, the sulfur compound present in the positive electrode may include lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 1<x≤2) or a mixture thereof. Even more specifically, the sulfur compound present in the positive electrode may include lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S 2 ) or a mixture thereof.

[0100] In one embodiment of the present disclosure, W SP It may be inorganic sulfur (S 8 )、Lithium (Poly) Sulfide (Li 2 S x , 1≤x≤8) or the total weight of a mixture thereof. Preferably, W SP It may be lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 1<x≤2) or the total weight of a mixture thereof. More preferably, W SP It may be lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S 2 ) or the total weight of a mixture thereof.

[0101] W SPThe measurement may be performed by a known method or a newly developed method of measuring the sulfur (S) content in the sulfur-based compound present in the positive electrode of the lithium-sulfur battery, and the measurement method is not limited to a specific method.

[0102] In one embodiment of the present disclosure, W SP It can be obtained by elemental analysis of a powder obtained by scraping the positive electrode from the current collector after disassembly / drying. In one embodiment of the present disclosure, the analysis can be performed using a sample obtained by scraping a number of electrodes from the current collector without inhomogeneity. For example, the sample can be analyzed using an elemental analyzer in combination with pyrolysis, and the corresponding inorganic sulfur (S 8 ) elements. Analysis of inorganic sulfur (S 8 ) is not limited to specific means and methods, and may include excluding inorganic sulfur (S 8 ). In this case, the analytical method for analyzing the sulfur (S) content may be performed on all elements except sulfur (S) and based on the weight % of sulfur (S) forming a mass balance with all analyzed elements.

[0103] In one embodiment of the present disclosure, as described above in W SE As described in the measurement method, W can be measured by disassembling the lithium-sulfur battery to be measured to separate the positive electrode / separator / negative electrode, extracting the sulfur-based compound present in the electrolyte from the separated positive electrode, drying at room temperature for more than 1 hour, and performing elemental analysis on the powder obtained by scraping the active material layer from the current collector. SP .

[0104] Thus, in one embodiment, as described above, the weight of sulfur present in the positive electrode (W SP ) may be the weight of sulfur (S) not extracted using a solvent for extracting sulfur compounds in order to measure the weight of sulfur in the electrolyte. In other words, the weight of sulfur present in the positive electrode (W SP ) may represent a sulfur-based compound that cannot be extracted in the solvent for more than 20 minutes, preferably within 20 minutes. From the dried positive electrode obtained after more than 1 hour, preferably after 1 hour, the current collector is completely scraped to obtain sulfur (S) that may be contained in the mixture from the positive electrode. The weight of the obtained mixture containing sulfur (S) is measured, and elemental analysis is performed to obtain the weight of sulfur present in the positive electrode (W SP ). Therefore, in one embodiment, the weight of sulfur present in the positive electrode (W SP ) can be based on the lithium-sulfur battery.

[0105] In another embodiment, the sulfur (S) content in the negative electrode can be measured by elemental analysis. Therefore, after disassembling the lithium-sulfur battery and determining the weight of sulfur (W) present in the electrolyte, SE ) After extracting the solvent-extractable sulfur-based compounds from the negative electrode as outlined above, the negative electrode can be dried and the weight of sulfur present in the negative electrode can be measured via elemental analysis. When the lithium-sulfur battery is manufactured or immediately after the manufacturing, the weight of sulfur present in the negative electrode can be about 0, preferably 0.

[0106] In yet another embodiment, the sulfur (S) content in the diaphragm may be about 0, preferably 0, as measured by elemental analysis. In order to measure the sulfur (S) content in the diaphragm, the diaphragm may be prepared by first disassembling the lithium-sulfur battery and extracting the sulfur-based compounds with a solvent as described above for measuring the sulfur content in the electrolyte. The diaphragm may then be dried and the sulfur (S) content in the diaphragm may then be measured. Without being bound by any theory, the diaphragm may not chemically react with sulfur, especially sulfur-based compounds, especially sulfur-based compounds derived from the sulfur-carbon complex of the positive electrode, and therefore sulfur (S) may not be chemically bound to the diaphragm. When extracted with a solvent by the method of measuring sulfur present in the electrolyte as described above, sulfur-based compounds that may be on the diaphragm or in the pores of the diaphragm may be completely removed.

[0107] In one embodiment of the present disclosure, elemental analysis may be performed using, for example, ion chromatography (IC) analysis, inductively coupled plasma optical emission spectrometer (ICP-OES) analysis, elemental analyzer (EA) analysis, ONH analysis, etc., but the elemental analysis method is not limited thereto.

[0108] In one embodiment of the present disclosure, for example, the amount of the sulfur-based compound present in the electrolyte of the lithium-sulfur battery may be measured according to the method described in Korean Patent Application No. 2021-0188588, but the present disclosure is not limited thereto.

[0109] In one embodiment of the present disclosure, for example, the amount of the sulfur-based compound present in the positive electrode of the lithium-sulfur battery may be measured according to the method described in Korean Patent Application No. 2021-0173961, but the present disclosure is not limited thereto.

[0110] In one embodiment of the present disclosure, R SL W measured as described above can be used SE and W SP Value export.

[0111] In one embodiment of the present disclosure, W SE and WSP The values ​​can each be measured in weight units and converted to equivalent weights, and their ratio can be R SL .

[0112] In one embodiment of the present disclosure, W SE and W SP The respective ranges of values ​​may vary depending on the size of the lithium-sulfur battery, the sulfur loading in the positive electrode, etc.

[0113] However, W SE and W SP The values ​​may each be expressed as a weight percentage based on the total sulfur (S) weight in the total sulfur-based compounds contained in the lithium-sulfur battery. Alternatively, they may be expressed as a weight percentage based on the total sulfur (S) weight derived from the total sulfur-based compounds added as the positive electrode active material when manufacturing the lithium-sulfur battery. In the present disclosure, they may be referred to as W' SE and W' SP .

[0114] In other words, according to the measurement method, the sulfur content is higher than R' SL W' can be used according to the following formula 1-2 SE and W' SP However, due to the total sulfur (S) value (which is W' SE and W' SP The weight percentage basis) is the same, so it is obvious that according to formula 1-2 R' SL The value has the same value as R according to Formula 1 SL The same value.

[0115] [Formula 1-2]

[0116] R' SL (%) = W' SE / W' SP × 100

[0117] Where W' SE is the weight % of sulfur (S) in the sulfur-based compound present in the electrolyte based on the total weight of sulfur (S) in the sulfur-based compound present in the lithium-sulfur battery, and W' SP is the weight % of sulfur (S) in the sulfur-based compound present in the positive electrode based on the total weight of sulfur (S) in the sulfur-based compound present in the lithium-sulfur battery.

[0118] In one embodiment of the present disclosure, in Formula 1-2, sulfur present in the sulfur-based compound in the lithium-sulfur battery may be measured by calculating the total sulfur (S) content in the sulfur-based compound used as a positive electrode active material in the step of manufacturing the lithium-sulfur battery.

[0119] In another embodiment of the present disclosure, when the amount of the sulfur-based compound used as the positive electrode active material in the step of manufacturing the lithium-sulfur battery is unknown, the amount of the sulfur-based compound used as the positive electrode active material can be measured by disassembling the lithium-sulfur battery and measuring the inorganic sulfur (S) by the above method. 8 ) and lithium (poly)sulfide (Li 2 S x , 1≤x≤8) and calculate the total sulfur (S) content to measure sulfur.

[0120] In one embodiment of the present disclosure, based on the total sulfur (S) weight in the sulfur-based compounds contained in the lithium-sulfur battery, W' SE For example, based on the total sulfur (S) weight of the sulfur-based compounds contained in the lithium-sulfur battery, W' SE It may be 0.1 wt % to 15 wt %, 1 wt % to 15 wt %, 1 wt % to 10 wt %, 2 wt % to 9.5 wt %, 3 wt % to 9.5 wt %, 5 wt % to 9.5 wt %, or 7 wt % to 9 wt %, but is not limited thereto.

[0121] In one embodiment of the present disclosure, based on the total sulfur (S) weight in the sulfur-based compounds contained in the lithium-sulfur battery, W' SP In another embodiment of the present disclosure, based on the total weight of sulfur (S) in the sulfur-based compound contained in the lithium-sulfur battery, W' SP For example, based on the total weight of sulfur (S) in the sulfur-based compound contained in the lithium-sulfur battery, W' SP It may be 65 wt % to 99 wt %, 70 wt % to 98 wt %, 75 wt % to 95 wt %, 75 wt % to 90 wt %, 75 wt % to 85 wt %, 75 wt % to 80 wt %, or 75.5 wt % to 80 wt %, but is not limited thereto.

[0122] In one embodiment of the present disclosure, W' SE and W' SP It may have a value satisfying the following Formula 2.

[0123] [Formula 2]

[0124] W' SP > 1.2 × W' SE +56.86

[0125] Where W' SE is the weight % of sulfur (S) in the sulfur-based compounds present in the electrolyte based on the total weight of sulfur (S) in the sulfur-based compounds contained in the lithium-sulfur battery, and

[0126] W' SP It is the weight % of sulfur (S) in the sulfur-based compound present in the positive electrode based on the total weight of sulfur (S) in the sulfur-based compound contained in the lithium-sulfur battery.

[0127] In one embodiment of the present disclosure, when the lithium-sulfur battery satisfies the above Formula 2, the specific capacity and energy density of the lithium-sulfur battery may be further improved, but the present disclosure is not limited thereto.

[0128] In one embodiment of the present disclosure, as described above with respect to measuring W SE and W SP The method described above, W' SE and W' SP Each can be measured based on a lithium-sulfur battery in a discharged state. For example, W' can be measured after disassembling a lithium-sulfur battery discharged to 1.7V to 1.9V, for example, 1.8V. SE and W' SP .

[0129] In one embodiment of the present disclosure, as described above, the total sulfur (S) weight in the sulfur-based compounds contained in the lithium-sulfur battery may refer to the weight of sulfur (S) contained in the positive electrode, negative electrode, electrolyte and separator of the lithium-sulfur battery.

[0130] In one embodiment of the present disclosure, the total weight of sulfur (S) present in the sulfur-based compounds present in the lithium-sulfur battery can be measured by separating each of the positive electrode, the negative electrode, the electrolyte, and the separator contained in the lithium-sulfur battery, extracting the sulfur-based compounds present in each of the positive electrode, the negative electrode, the electrolyte, and the separator, measuring the amount of sulfur present in the extracted sulfur-based compounds, and adding the measured amounts.

[0131] In another embodiment of the present disclosure, the total sulfur (S) contained in the lithium-sulfur battery may preferably be derived from the sulfur-based compound used as the positive electrode active material when manufacturing the lithium-sulfur battery. Therefore, the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery may be equal to the sulfur (S) content in the sulfur-based compound added to the positive electrode when manufacturing the lithium-sulfur battery or immediately after the manufacturing.

[0132] In one embodiment of the present disclosure, the total sulfur (S) weight in the lithium-sulfur battery may refer to the inorganic sulfur (S) present in each of the positive electrode, the negative electrode, the electrolyte and the separator contained in the lithium-sulfur battery. 8 ) and lithium (poly)sulfide (Li 2 S x , 1≤x≤8).

[0133] In one embodiment of the present disclosure, the total weight of sulfur (S) present in the sulfur-based compounds contained in the lithium-sulfur battery may refer to the inorganic sulfur (S) added as the positive electrode active material when manufacturing the lithium-sulfur battery. 8 ) is the weight of sulfur (S) calculated from the amount of

[0134] In one embodiment of the present disclosure, R SL It can be measured immediately after manufacturing the lithium-sulfur battery, but can be measured based on a battery aged after one or more charge and discharge cycles. SL A lithium-sulfur battery having a value of 15% or less can provide excellent effects in terms of specific capacity and / or energy density, and thus there is no particular limitation on the timing of measurement.

[0135] As mentioned above, W SE and W SP Derived from the sulfur-based material used as the positive electrode active material when manufacturing the lithium-sulfur battery. SE and W SP Derived from the sulfur-carbon complex in the positive electrode. Specifically, W SE and W SP The amount of sulfur derived from the lithium salt or the sulfur-based salt as an additive added to the electrolyte when manufacturing the lithium-sulfur battery is not measured. More specifically, according to the above-mentioned measurement method, the amount of sulfur derived from the sulfur-based material of the positive electrode can be measured instead of the amount of sulfur derived from the lithium salt or the sulfur-based salt contained in the additive.

[0136] More specifically, the sulfide salts include, for example, CF 3 SO 3 , CH 3 SO 3 Li, CF 3 SO 3 Li, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 ) 2 NLi,(SO 2 F) 2 NLi, (CF 3SO 2 ) 3 CLi, especially (CF 3 SO 2 ) 2 NLi (LiTFSI), and these sulfide salts can be combined with the sulfide materials (inorganic sulfur (S 8 ), lithium polysulfide (Li 2 S x , 1≤x≤8) etc.) to distinguish.

[0137] Subsequently, each component of the lithium-sulfur battery will be described in detail.

[0138] positive electrode

[0139] In one embodiment of the present disclosure, the positive electrode may include a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector.

[0140] The positive electrode current collector is not limited to a specific type, and may include a positive electrode current collector that supports the positive electrode active material and has high conductivity without causing chemical changes in the battery. For example, the positive electrode current collector may include copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, or copper or stainless steel with a surface treated with carbon, nickel or silver, and an aluminum-cadmium alloy.

[0141] The positive electrode current collector may have fine concavoconvexities on the surface to enhance bonding strength to the positive electrode active material, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, and a non-woven fabric.

[0142] The positive electrode active material layer includes the positive electrode active material, and may further include a conductive material, a binder, and an additive.

[0143] In one embodiment of the present disclosure, the positive electrode active material includes a sulfur-carbon composite.

[0144] In one embodiment of the present disclosure, the sulfur-carbon composite may include a porous carbon material; and a sulfur-based compound loaded on at least one of the pores of the porous carbon material or the outer surface of the porous carbon material. Since sulfur used as the positive electrode active material itself does not have conductivity, sulfur can be used in combination with a conductive material such as a carbon material, and the porous carbon material can be used as a sulfur carrier. In addition, the sulfur-based compound can be added as the positive electrode active material, and can include, for example, inorganic sulfur (S 8 ), lithium sulfide (Li 2 S), lithium polysulfide (Li 2 S x , 1<x≤8), disulfide, carbon-sulfur polymer ((C 2 Sy ) n , y = 2.5 to 50, n ≥ 2) or two or more thereof. Preferably, the sulfur-based compound may include inorganic sulfur (S 8 ).

[0145] In one embodiment of the present disclosure, the porous carbon material is not limited to a specific type and may include any type of porous carbon material that is capable of loading the sulfur-based compound as the positive electrode active material, providing a skeleton for uniformly and stably fixing the sulfur-based compound, and improving the conductivity of the positive electrode.

[0146] Typically, the porous carbon material can be manufactured by carbonizing precursors of various carbon materials. The porous carbon material may include irregular pores. The average diameter of the pores may be in the range of 1 nm to 200 nm, and the porosity may be in the range of 10% to 90% by volume of the total volume of the porous carbon material. In the case where the average diameter of the pores is less than the above range, the pore size is at the molecular level, which makes it impossible for sulfur to penetrate. On the contrary, in the case where the average diameter of the pores exceeds the above range, the porous carbon material has low mechanical strength, which is not conducive to use in the electrode manufacturing process.

[0147] In one embodiment of the present disclosure, "average diameter of the hole" can be measured by known methods for measuring the pore size of porous materials, and the measuring method is not limited to a specific method. For example, the pore size can be measured by scanning electron microscopy (SEM), field emission electron microscopy (FEM), laser diffraction or Brunauer-Emmett-Teller (BET) method. The measurement performed using the laser diffraction method can use, for example, a commercially available laser diffraction particle size measuring machine (e.g., Microtrac MT3000). In addition, the measurement performed by the BET method can, for example, use the BELSORP series analyzer of BEL Japan, but is not limited thereto.

[0148] In one embodiment of the present disclosure, "porosity" refers to the fraction of voids in a structure to the total volume, and is expressed in %, and can be used interchangeably with void fraction, porosity, etc. In the present disclosure, porosity measurement is not limited to a specific method, and according to one embodiment of the present disclosure, for example, porosity can be measured by a BET method using nitrogen or a Hg porosimeter and ASTM D2873.

[0149] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular, or block-like, and may include, but not limited to, any shape commonly used in the lithium-sulfur battery.

[0150] The porous carbon material may include any carbon material with a porous structure or a high specific surface area that is commonly used in the corresponding technical field. For example, the porous carbon material may include at least one selected from the group consisting of: graphite; graphene; carbon black, including denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; carbon nanotubes (CNTs), including single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers, including graphite nanofibers (GNFs), carbon nanofibers (CNFs) and activated carbon fibers (ACFs); graphite, including natural graphite, artificial graphite, expanded graphite and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.

[0151] In one embodiment of the present disclosure, the porous carbon material may include, for example, carbon nanotubes (CNTs).

[0152] In one embodiment of the present disclosure, the sulfur-carbon composite may, for example, have a sulfur / carbon weight ratio (S / C weight ratio) of 5 g / g or less, more specifically 2.5 g / g or less. For example, the sulfur-carbon composite may have an S / C weight ratio of 2.4 g / g. When the S / C ratio of the sulfur-carbon composite is within the above range, it may be desirable from the perspective of the ability of the sulfur-carbon composite to transport electrons (conductivity) and electrochemical specific surface area, for example, the larger available surface of the sulfur-carbon composite may more effectively inhibit sulfur from dissolving out of the positive electrode, but the present disclosure is not limited thereto.

[0153] In one embodiment of the present disclosure, the S / C ratio may be calculated from the weight (g) of sulfur and the weight (g) of carbon present in the sulfur-carbon composite. Alternatively, the S / C ratio may be calculated from the weight (wt%) of sulfur and the weight (wt%) of carbon based on the total weight of the sulfur-carbon composite. The S / C ratio may be dimensionless.

[0154] In one embodiment of the present disclosure, the S / C weight ratio may have a value of 0.5 to 2.5, 1.0 to 2.50, 1.5 to 2.45, 2.0 to 2.45, or 2.35 to 2.45. For example, the S / C ratio may be composed of the weight of inorganic sulfur (S 8 ) / the weight of the porous carbon material. For example, the S / C ratio can be calculated by S 8 / CNT weight ratio was calculated.

[0155] The method of manufacturing the sulfur-carbon composite is not limited to the specific method in the present disclosure, and may include methods commonly used in the corresponding technical field. For example, the sulfur-carbon composite can be manufactured by simply mixing sulfur with a porous carbon material and performing a heat treatment to produce a composite.

[0156] On the basis of the above composition, the positive electrode active material may further include at least one selected from transition metals, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, or alloys of these elements and sulfur.

[0157] The transition metal may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au or Hg, the Group 13 element may include Al, Ga, In, Ti, and the Group 14 element may include Ge, Sn, Pb.

[0158] In one embodiment of the present disclosure, in the case of S In terms of the relationship between the sulfur-carbon composite and the carbon-sulfur composite, the S / C ratio may satisfy the following formula 3:

[0159] [Formula 3]

[0160] 10.667 × R S / C - 10.633 > R SL

[0161] Where R SL is the content ratio of sulfur (S), and

[0162] R S / C is the weight ratio of sulfur (S) to carbon (C) in the sulfur-carbon composite.

[0163] It was unexpectedly found that when the lithium-sulfur battery satisfies Formula 3, significant improvements in specific capacity and energy density can be achieved.

[0164] In one embodiment of the present disclosure, the content of the sulfur-carbon complex may be 50 wt % or more based on the total weight of the positive electrode. Specifically, the positive electrode may include the current collector and the positive electrode active material layer on the current collector, and when the positive electrode active material layer includes the sulfur-carbon complex, the content of the sulfur-carbon complex may be, for example, 80 wt % or more, 90 wt % or more, or 95 wt % or more based on the total weight of the positive electrode active material layer. Specifically, the content of the sulfur-carbon complex may be 80 wt % to 100 wt %, more specifically 85 wt % to 99 wt %, 90 wt % to 100 wt %, 90 wt % to 99 wt %, 95 wt % to 98 wt %, 95 wt % to 97 wt %, or 96 wt %, based on the total weight of the positive electrode active material layer. When the amount of the sulfur-carbon composite is less than the above range, a larger amount of auxiliary materials such as a conductive material and a binder and a smaller amount of the sulfur-carbon composite make it difficult to achieve a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite is higher than the above range, the amount of the conductive material or the binder as described below is relatively insufficient, resulting in poor physical properties of the electrode.

[0165] In one embodiment of the present disclosure, the positive electrode may have, for example, 1.67 mg s / cm 2 Above, specifically 1.67 to 2.92 mg s / cm 2 , more specifically 1.67 to 2.08 mg s / cm 2 The loading amount can be calculated from the amount of active material in the positive electrode and the amount of sulfur (S) in the active material.

[0166] In one embodiment of the present disclosure, when the loading capacity of the positive electrode is converted into capacity, for example, the loading capacity may be 2.0 mAh / cm 2 Above, specifically 2.0mAh / cm 2 Up to 3.5mAh / cm 2 , more specifically 2.0 mAh / cm 2 Up to 2.5 mAh / cm 2 , but the present disclosure is not limited thereto.

[0167] The conductive material may be a material that serves as a movement path for electrons from a current collector to a positive electrode active material by electrically connecting an electrolyte to the positive electrode active material, and may include any material having conductive properties as an electrode constituent physically different from carbon contained in the sulfur-carbon composite without limitation.

[0168] In one embodiment of the present disclosure, the conductive material may include, for example, carbon black, such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black; carbon derivatives, such as carbon nanotubes or fullerenes; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorocarbons, aluminum, nickel powders; or conductive polymers, such as polyaniline, polythiophene, polyacetylene, polypyrrole, and the conductive materials are used alone or in combination.

[0169] In one embodiment of the present disclosure, the amount of the conductive material may be 0 wt % to 10 wt %, for example 1 wt % to 10 wt %, based on the total weight of the positive active material. When the amount of the conductive material is lower than the above range, the voltage and capacity are reduced due to the poor electron transport between the positive active material and the current collector. On the contrary, when the amount of the conductive material is higher than the above range, the ratio of the positive active material is reduced, resulting in a decrease in the total energy (charge) of the battery, and it is therefore desirable to determine the optimal amount within the above range.

[0170] In one embodiment of the present disclosure, the binder may be used to bond the positive active material to the positive current collector and connect the positive active material in an organic manner to improve bonding strength, and may include any binder generally used in the corresponding technical field.

[0171] For example, the adhesive may include one selected from the group consisting of, or a mixture or copolymer thereof: a fluororesin adhesive including polyvinylidene fluoride (PVdF), a polyvinylidene fluoride polymer including at least one vinylidene fluoride repeating unit, polytetrafluoroethylene (PTFE) or a mixture thereof; a rubber adhesive including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, styrene-isoprene rubber; an acrylic adhesive; a cellulose adhesive including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose; a polyol adhesive; a polyolefin adhesive including polyethylene, polypropylene; a polyimide adhesive; a polyester adhesive; a silane adhesive; a polyacrylic acid adhesive; and a polyacrylonitrile adhesive. In one embodiment of the present disclosure, the adhesive may include, for example, polyacrylate (PAA).

[0172] In one embodiment of the present disclosure, the amount of the binder may be 1 wt % to 10 wt % based on the total weight of the positive electrode active material layer. When the amount of the binder is less than the above range, the positive electrode active material and the conductive material may fall off due to the weak physical properties of the positive electrode, and when the amount of the binder is higher than the above range, a lower ratio of the positive electrode active material and the conductive material in the positive electrode may reduce battery capacity, so it is desirable to determine the optimal amount in the above range.

[0173] In the present disclosure, a method of manufacturing a positive electrode for a lithium secondary battery is not limited to a specific method, and may include a method known to those skilled in the art or various improved methods.

[0174] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition including the above composition, and coating the composition on at least one surface of a positive electrode collector to form a positive electrode active material layer.

[0175] The positive electrode slurry composition includes the positive electrode active material described above, and may further include a binder, a conductive material, and a solvent.

[0176] The solvent includes any solvent that can uniformly disperse the positive electrode active material. The solvent may preferably be an aqueous solvent, such as water, and in this case, the water may be distilled water, deionized water. The solvent is not limited thereto, and if necessary, may contain a lower alcohol that is easily mixed with water. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, they may be used in combination with water.

[0177] The solvent may be included in an amount to ensure a sufficient concentration level to facilitate coating, and the amount of the solvent may vary depending on the coating method and apparatus.

[0178] If necessary, the positive electrode slurry composition may further include materials commonly used in the corresponding technical field to improve functions. For example, the positive electrode slurry composition may further include a viscosity modifier, a flow aid, a filler, and the like.

[0179] In the present disclosure, the method of coating the positive electrode slurry composition is not limited to a specific method, for example, may include a doctor blade, die casting, comma coating, screen printing. In addition, the positive electrode slurry may be formed on a separate substrate and coated on a positive electrode current collector by pressing or laminating.

[0180] After coating, a drying process may be performed to remove the solvent. The drying process may be performed at a temperature and time sufficient to remove the solvent, and the conditions may vary depending on the type of the solvent, and the present disclosure is not limited to specific conditions. For example, the drying method may include drying by warm air, hot air and low humidity air, vacuum drying, and drying by (far) infrared radiation and electron beam radiation. The drying speed is adjusted to remove the solvent as quickly as possible within a speed range that prevents cracks from being generated in the positive active material layer or the positive active material layer from being peeled off from the positive current collector due to stress concentration.

[0181] In addition, after the drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. The pressing may include molding and rolling.

[0182] The positive electrode manufactured by the above composition and manufacturing method, specifically the positive electrode active material layer, can have a porosity of 50% to 80% by volume, specifically 60% to 75% by volume. When the porosity of the positive electrode is less than 50% by volume, due to the high filling degree of the positive electrode slurry composition containing the positive electrode active material, the conductive material and the binder, it is impossible to maintain a sufficient amount of electrolyte for ionic conductivity and / or conductivity in the positive electrode active material, resulting in degradation of the output characteristics or cycle characteristics of the battery, and the problem of reduced overvoltage and discharge capacity of the battery becomes worse. On the contrary, when the porosity of the positive electrode is higher than 80% by volume, the excessively high porosity reduces the physical and electrical connection with the current collector, resulting in low adhesion strength and poor reaction, and the high electrolyte filling degree reduces the energy density of the battery, so the porosity of the positive electrode is appropriately adjusted within the above range.

[0183] negative electrode

[0184] The negative electrode may include a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate or an aluminum foil.

[0185] The negative electrode current collector is used to support the negative electrode active material layer, and is the same as described in the positive electrode current collector.

[0186] In addition to the negative electrode active material, the negative electrode active material layer may include a conductive material and a binder. In this case, the conductive material and the binder are the same as described above.

[0187] The negative electrode active material may include a material capable of reversibly inserting or deinserting lithium (Li + ), a material that reversibly forms a lithium-containing compound by reacting with lithium ions, lithium metal or a lithium alloy.

[0188] Able to reversibly insert or deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material that reversibly forms the lithium-containing compound by the reaction of ) may be, for example, tin oxide, titanium nitrate or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).

[0189] Preferably, the negative electrode active material may be lithium metal, specifically in the form of lithium metal foil or lithium metal powder.

[0190] Diaphragm

[0191] The separator separates or insulates the positive electrode from the negative electrode and enables lithium ions to be transmitted between the positive electrode and the negative electrode, and may include a porous non-conductive or insulating material. The separator may include any separator commonly used in lithium secondary batteries without limitation. The separator may be an independent component such as a film, and may be a coating added to the positive electrode and / or the negative electrode.

[0192] Preferably, the separator may have low resistance to electrolyte ion transport and high electrolyte wettability.

[0193] In one embodiment of the present disclosure, the separator may include a porous substrate, and the porous substrate may include any type of porous substrate commonly used in secondary batteries. The separator may include a single or stacked porous polymer film, such as a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, or a polyolefin-based porous film, but is not limited thereto.

[0194] In the present disclosure, the porous substrate is not limited to a specific material and may include any porous substrate commonly used in electrochemical devices. For example, the porous substrate may include at least one material selected from the group consisting of polyolefins such as polyethylene, polypropylene, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole) and polyarylates.

[0195] In one embodiment of the present disclosure, the thickness of the porous substrate is not limited to a specific range, but may be 1 μm to 100 μm, preferably 5 μm to 50 μm. The thickness range of the porous substrate is not limited to the above range, but when the thickness is too small and below the above lower limit, poor mechanical properties may cause damage to the separator during battery use.

[0196] In one embodiment of the present disclosure, the average diameter and porosity of pores present in the porous substrate are also not limited to specific ranges, but may be 0.001 μm to 50 μm and 10% to 95% by volume, respectively.

[0197] In one embodiment of the present disclosure, the separator may further include a porous coating layer on at least one surface of the porous substrate, the porous coating layer including inorganic particles and a binder.

[0198] In one embodiment of the present disclosure, the inorganic particles and binder contained in the porous coating layer are not limited to specific types and may include inorganic particles and binders generally used in the porous coating layer of the separator, and the manufacturing method thereof is not limited to a specific method.

[0199] Electrolyte

[0200] The electrolyte solution includes a non-aqueous solvent as a moving medium of ions participating in an electrochemical reaction of a lithium-sulfur battery and a lithium salt as an electrolyte.

[0201] The electrolyte may include any composition used in lithium secondary batteries, specifically lithium sulfur batteries, without limitation.

[0202] In one embodiment of the present disclosure, the nonaqueous solvent is not limited to a specific type and may include any type of solvent used in the lithium-sulfur battery, and may include, for example, ether solvents, esters, amides, linear carbonates, and cyclic carbonates.

[0203] In one embodiment of the present disclosure, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone or a mixture thereof, but is not limited thereto.

[0204] In one embodiment of the present disclosure, the linear carbonate may generally include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate or a mixture thereof, but is not limited thereto.

[0205] In one embodiment of the present disclosure, the cyclic carbonate may include, for example, any one or a mixture thereof selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate, and halides thereof. The halides may include, for example, fluoroethylene carbonate, but are not limited thereto.

[0206] In one embodiment of the present disclosure, the nonaqueous solvent may include an ether solvent.

[0207] In one embodiment of the present disclosure, the content of the ether solvent may be 60% by volume or more, for example, 60% by volume to 100% by volume, 70% by volume to 100% by volume, 80% by volume to 100% by volume, 85% by volume to 100% by volume, 90% by volume to 100% by volume, or 95% by volume to 100% by volume, based on the total volume of the non-aqueous solvent. When the amount of the ether solvent is within the above range, the solubility of components of the electrolyte such as lithium salts may be improved, but the present disclosure is not limited thereto.

[0208] In one embodiment of the present disclosure, the ether solvent may include acyclic ether, cyclic ether or a mixture thereof.

[0209] In one embodiment of the present disclosure, the non-cyclic ether may include, for example, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol, diethylene glycol diethyl ether, triethylene glycol, tetraethylene glycol, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether and ethylene glycol ethyl methyl ether. Preferably, the non-cyclic ether may include at least one selected from the group consisting of dimethoxyethane, diethoxyethane, diethylene glycol, triethylene glycol and tetraethylene glycol, more preferably dimethoxyethane.

[0210] In one embodiment of the present disclosure, the cyclic ether may include, for example, at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxy Tetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene and dimethyl isosorbide. Preferably, the cyclic ether may include at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran and 2,5-dimethyltetrahydrofuran, more preferably 2-methylfuran.

[0211] In one embodiment of the present disclosure, the non-aqueous solvent may include, for example, dimethoxyethane (DME), ethylene glycol, propylene glycol, or a mixture thereof.

[0212] In one embodiment of the present disclosure, the nonaqueous solvent may include a mixture of the non-cyclic ether and the cyclic ether.

[0213] In one embodiment of the present disclosure, the non-aqueous solvent may include dimethoxyethane (DME) and 2-methylfuran (2-MeF).

[0214] In one embodiment of the present disclosure, the volume ratio (volume / volume) of the non-cyclic ether to the cyclic ether may be 5:95 to 95:5 (volume / volume), specifically 95:5 to 50:50, more specifically 90:10 to 70:30, 85:15 to 75:25, or 80:20. In the present disclosure, the volume ratio corresponds to the ratio of "volume % of non-cyclic ether": "volume % of cyclic ether" in the ether solvent.

[0215] In one embodiment of the present disclosure, in terms of the solubility of the electrolyte, the non-aqueous solvent may not include the carbonate-based solvent. Alternatively, the non-aqueous solvent may include a very small amount of a carbonate-based solvent so that the carbonate-based solvent does not affect the solubility of the lithium salt, for example, when the non-aqueous solvent includes a carbonate-based solvent, based on the gross weight of the lithium secondary battery electrolyte, the amount of the carbonate-based solvent may be less than 3 wt %, less than 2 wt %, less than 1 wt %, less than 0.5 wt % or 0 wt % (i.e., none).

[0216] In one embodiment of the present disclosure, the lithium salt is not limited to a specific type and may include a lithium salt used as an electrolyte for a lithium secondary battery. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 ,LiC 4 BO 8 、LiAsF 6 、LiSbF 6 、LiAlCl 4 , CH 3 SO 3 Li, CF 3 SO 3 Li, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 ) 2 NLi,(SO 2 F) 2 NLi, (CF 3 SO 2 ) 3 CLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide or two or more thereof.

[0217] In one embodiment of the present disclosure, the concentration of the lithium salt may be appropriately determined in consideration of ion conductivity and solubility, and may be, for example, 0.1 to 4 M, preferably 0.25 to 2 M, 0.5 to 2 M, 0.5 to 1.5 M, or 0.5 to 1.0 M. When the concentration of the lithium salt is within the above range, ion conductivity suitable for battery operation or appropriate viscosity of the electrolyte may be ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present disclosure is not limited thereto.

[0218] In one embodiment of the present disclosure, the electrolyte may further contain a nitrogen compound on the basis of containing the lithium salt to improve the conductivity of the electrolyte and increase the life of the lithium-sulfur battery. Specifically, the effect of the nitrogen compound is not limited thereto. For example, the nitrogen compound may inhibit the reduction reaction of polysulfides generated during the charge and discharge of the lithium-sulfur battery, thereby preventing the irreversible consumption of polysulfides, resulting in improved performance of the lithium-sulfur battery.

[0219] In one embodiment of the present disclosure, the nitrogen compound is not limited to a specific type, and may include a nitrogen compound that forms a stable film on a negative electrode or a lithium metal electrode of a lithium secondary battery, specifically a lithium sulfur battery, and improves charge and discharge efficiency, and may include, for example, a nitric acid compound, a nitrous acid compound, or a mixture thereof.

[0220] In one embodiment of the present disclosure, the nitrogen compound may be, for example, selected from the group consisting of inorganic nitric acid or nitrous acid compounds, such as lithium nitrate (LiNO 3 ), potassium nitrate (KNO 3 ), cesium nitrate (CsNO 3 ), barium nitrate (Ba(NO 3 ) 2 ), ammonium nitrate (NH 4 NO 3 ), lithium nitrite (LiNO 2 ), potassium nitrite (KNO 2 ), cesium nitrite (CsNO 2 ), ammonium nitrite (NH 4 NO 2 ); organic nitric acid or nitrous acid compounds, such as methyl nitrate, dialkyl imidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite; organic nitro compounds, such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, and preferably may contain lithium nitrate.

[0221] In one embodiment of the present disclosure, based on the total weight of the electrolyte for lithium secondary batteries, the content of the nitrogen compound may be, for example, 1 wt % to 10 wt %, 2 wt % to 10 wt %, or 3 wt % to 10 wt %, specifically 3 wt % to 8 wt %, 3 wt % to 6 wt %, or 3 wt % to 5 wt %, but is not limited thereto. When the nitrogen compound is included in the above amount, the nitrogen compound may improve the conductivity of the electrolyte and inhibit the reduction reaction of polysulfides when used in the lithium-sulfur battery, but the present disclosure is not limited thereto.

[0222] In one embodiment of the present disclosure, the lithium-sulfur battery may have a variable energy density according to the ratio of the electrolyte to the positive electrode active material. The smaller the ratio of the electrolyte to the positive electrode active material, the higher the energy density of the lithium-sulfur battery. For example, the weight ratio of the electrolyte to the sulfur in the sulfur-carbon composite (E1 / S weight ratio) may be 3.5 g / g or less.

[0223] In one embodiment of the present disclosure, the lithium-sulfur battery may be manufactured, for example, with an El / S ratio of 3 g / g or less or 2.9 g / g or less.

[0224] According to one embodiment of the present disclosure, the lithium-sulfur battery of the above configuration may have a specific capacity of 60% or more, specifically 65% ​​or more, 70% or more, or 75% or more, compared to the theoretical specific capacity calculated from the total amount of sulfur-based compounds contained in the lithium-sulfur battery. More specifically, the lithium-sulfur battery may have a specific capacity of 80% or more, further 90% or more, compared to the theoretical specific capacity calculated from the total amount of sulfur-based compounds contained in the lithium-sulfur battery.

[0225] In one embodiment of the present disclosure, the specific capacity of the lithium-sulfur battery may be, for example, 1,000 mAh / g or more. For example, the specific capacity of the lithium-sulfur battery may be 1,050 mAh / g or more, 1,080 mAh / g or more, specifically 1,000 mAh / g to 1,675 mAh / g, 1,000 mAh / g to 1,300 mAh / g, 1,050 mAh / g to 1,250 mAh / g, or 1,080 mAh / g to 1,150 mAh / g.

[0226] In one embodiment of the present disclosure, the energy density of the lithium-sulfur battery may be, for example, 300Wh / kg or more. For example, the energy density of the lithium-sulfur battery may be 300Wh / kg to 2,600Wh / kg, 300Wh / kg to 1,600Wh / kg, 300Wh / kg to 1,000Wh / kg, 300Wh / kg to 800Wh / kg, 300Wh / kg to 450Wh / kg, or 330Wh / kg to 400Wh / kg.

[0227] In one embodiment of the present disclosure, the specific capacity and energy density of the lithium-sulfur battery may be measured by known methods of measuring the specific capacity and energy density of lithium-sulfur batteries, respectively, and the measuring method is not limited to a specific method.

[0228] In one embodiment of the present disclosure, the specific capacity and energy density of the lithium-sulfur battery may be measured, for example, by discharging at a 0.5C rate and charging at a 0.3C rate in the range between 1.8V and 2.5V at room temperature of 23°C.

[0229] In one embodiment of the present disclosure, the lithium-sulfur battery may have various shapes, such as a coin shape, a pouch shape, or a cylindrical shape, but is not limited thereto.

[0230] According to another aspect of the present disclosure, a method for evaluating the specific capacity of a lithium-sulfur battery using the above Formula 1 is provided.

[0231] The evaluation method comprises the following steps: SL ) is a step in determining lithium-sulfur batteries below 15% as batteries with high specific capacity.

[0232] In one embodiment of the present disclosure, the battery having a high specific capacity may be, for example, a battery having a specific capacity of 1,000 mAh / g or more.

[0233] Hereinafter, embodiments will be described to facilitate understanding of the present disclosure, but the following embodiments are provided by way of example, and it is apparent to those skilled in the art that various changes and modifications may be made thereto within the technical aspects and scope of the present disclosure, and such changes and modifications fall within the scope of the appended claims.

[0234] [Manufacturing of lithium secondary batteries]

[0235] Example 1

[0236] Inorganic sulfur (S) is used as the positive electrode active material. 8 ) and carbon nanotubes (CNTs) were mixed to prepare a sulfur-carbon composite (S / C weight ratio = 2.45), and 96 wt % of the prepared sulfur-carbon composite and 4 wt % of polyacrylate (PAA) as a binder were mixed to prepare a positive electrode slurry composition. The positive electrode slurry composition was coated on an aluminum current collector and dried to manufacture a positive electrode. The loading amount of the manufactured positive electrode was 2.08 mg (s) / cm 2 (2.5mAh / cm 2 ).

[0237] For the negative electrode, 60 μm thick lithium metal was used.

[0238] The positive electrode and the negative electrode were placed opposite to each other with a polyethylene separator having a thickness of 16 μm and a porosity of 46 volume % interposed therebetween to prepare an electrode assembly.

[0239] The prepared electrode assembly was housed in a bag-type case, and 0.75 M lithium salt (LiTFSI) and 3 wt % lithium nitrate (LiNO) dissolved in a mixed solvent of dimethoxyethane (DME):2-methylfuran (2-MeF) with a volume ratio of 8:2 were injected at an El / S ratio of 2.9 g / g. 3 ) electrolyte to manufacture lithium-sulfur batteries.

[0240] Comparative Example 1

[0241] A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the sulfur-carbon composite was prepared at an S / C weight ratio of 2.9.

[0242] Comparative Example 2

[0243] A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the sulfur-carbon composite was prepared at an S / C weight ratio of 2.6.

[0244] R(SL) measurement and battery performance evaluation

[0245] The lithium-sulfur batteries manufactured in Example 1 and Comparative Examples 1 and 2 were each charged once at a 0.3C rate in the range of 1.8 V to 2.5 V at room temperature (23°C) and discharged once at a 0.5C rate to 1.8 V, and in this case, the battery capacity (mAh) and energy (Wh) were measured and divided by the battery capacity of each battery to evaluate the specific capacity (mAh / g) and energy density (Wh / kg) of the battery, and the evaluation results are shown in Table 1 below.

[0246] Subsequently, after disassembling the lithium-sulfur battery discharged to 1.8 V, R was measured according to the following formula 1: SL .

[0247] [Formula 1]

[0248] R SL (%) = W SE / W SP × 100

[0249] Where W SE is the weight of sulfur (S) in the sulfur-based compounds present in the electrolyte, and

[0250] W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

[0251] To measure W SE The disassembled battery was placed in an extraction solvent (DME) and extracted for 48 hours. The battery was removed from the extraction solution and methyl trifluoromethanesulfonate (CF 3 SO 3 CH 3 ) was added to the extract to produce methyl derivatization. The methyl derivatized components were analyzed and separated by LC (liquid chromatography) under the following conditions and then fractionated according to the fraction range.

[0252] [LC / UV analysis conditions]

[0253] Column: CAPCELLPAL C18 column (inner diameter 4.6 mm, length 50 mm, particle size 3 μm, Osaka SODA Co., Ltd.)

[0254] Mobile phase: H 2 O / methanol mixed solvent, gradient elution (0 min: H2 O / methanol 75 / 25 (v / v), 10 min: HO 2 O / methanol = 0 / 100 (v / v), 20 min: HO 2 O / methanol=0 / 100 (volume / volume)

[0255] Flow rate: 0.7ml / min

[0256] Column temperature: 40°C

[0257] Injection volume: 10 μl

[0258] Detection wavelength: 254nm

[0259] Then, using the standard for each concentration manufactured in Korean Patent Application No. 2021-0188588, the peak area of ​​each methyl-derivatized component shown in the chromatogram obtained by LC / UV analysis was measured, the amount of each component of lithium polysulfide present in the extract was calculated, and they were added together to measure W. SE value.

[0260] To measure W SP , at room temperature will be W SE After the positive electrode extracted and separated by measurement is dried, the sulfur (S) content in the positive electrode is measured according to the method described in Korean Patent Application No. 2021-0173961. Specifically, the positive electrode active material layer is scraped off and placed in a Sn capsule, placed in an EA device (Flash 2100, Thermo Company), and burned at 990 ° C to generate gas. The generated gas is separated using a GC column, and the sulfur (S) content is measured. In this case, BBOT (2,5-bis (5-tert-butyl-benzoxazol-2-yl) thiophene) is used as a standard material for quantitative analysis.

[0261] Table 1 below shows the amount of inorganic sulfur (S) used in preparing the sulfur-carbon composite used in each battery. 8 ) is derived from the total sulfur (S) weight measured W' SE and W' SP The weight ratio of each, and thus calculate R' according to formula 1-2 SL , due to R' SL According to Formula 1, R SL The following table 1 shows the R SL .

[0262] [Formula 1-2]

[0263] R' SL (%) = W' SE / W' SP × 100

[0264] Where W' SE is the weight % of sulfur (S) in the sulfur-based compound present in the electrolyte based on the weight of sulfur (S) in the sulfur-based compound present in the lithium-sulfur battery, and

[0265] W' SP is the weight % of sulfur (S) in the sulfur-based compound present in the positive electrode based on the weight of sulfur (S) in the sulfur-based compound present in the lithium-sulfur battery.

[0266] In addition, by using W' measured as described above SE and W' SP The values ​​were evaluated whether the following Formulas 2 and 3 were satisfied to evaluate T(true) / F(false), and the results are shown in Table 1 below.

[0267] [Formula 2]

[0268] W' SP > 1.2 × W' SE +56.86

[0269] [Formula 3]

[0270] 10.667 × R S / C - 10.633 > R SL

[0271]

[0272] From Table 1 above, it can be seen that the R SL In the case of Example 1 in which the S / C ratio is 15% or less, the S / C ratio is lower than those of Comparative Examples 1 and 2, and it has a specific capacity of 1,000 mAh / g or more and a high energy density. However, when Comparative Examples 1 and 2 are compared, although Comparative Example 1 has a high S / C ratio, Comparative Example 1 has a lower specific capacity and energy density than Comparative Example 2. Therefore, it can be confirmed that by R SL The value can determine the lithium-sulfur battery with high specific capacity.

[0273] When the battery is discharged to 1.8V, the reduction reaction of sulfur no longer occurs, and in this case, the battery exhibits maximum capacity, and R SL Therefore, it can be confirmed that in order to realize lithium-sulfur batteries with high specific capacity and high energy density, R SL Control below 15%.

Claims

1. A lithium-sulfur battery, comprising: A positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode or the electrolyte comprises a sulfur compound, According to the following formula 1, the content ratio of sulfur (S) is (R SL ) is less than 15%: [Formula 1] R SL (%) = W SE / W SP × 100 Wherein W SE is the weight of sulfur (S) in the sulfur-based compounds present in the electrolyte, and Wherein W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode.

2. The lithium-sulfur battery according to claim 1, wherein W in Formula 1 SE and W SP Each represents a value measured in a 1.7V to 1.9V discharge state.

3. The lithium-sulfur battery according to claim 1, wherein the sulfur compound present in the electrolyte comprises inorganic sulfur (S8), lithium (poly)sulfide (Li2S x , 1≤x≤8) or a mixture thereof.

4. The lithium-sulfur battery according to claim 1, wherein the sulfur compound present in the positive electrode comprises inorganic sulfur (S8), lithium (poly)sulfide (Li2S x , 1≤x≤8) or a mixture thereof.

5. The lithium-sulfur battery according to claim 1, wherein the W is based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery. SE It is 15% by weight or less.

6. The lithium-sulfur battery according to claim 1, wherein the W is based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery. SP It is 65% by weight or more.

7. The lithium-sulfur battery according to claim 6, wherein the W is based on the total sulfur (S) weight in the sulfur-based compound contained in the lithium-sulfur battery. SP It is 75.5% by weight or more.

8. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery satisfies the following formula 2: [Formula 2] IN' SP > 1.2 × W' SE + 56.86 Wherein W' SE is the weight % of sulfur (S) in the sulfur-based compounds present in the electrolyte based on the total weight of sulfur (S) in the sulfur-based compounds contained in the lithium-sulfur battery, and Wherein W' SP It is the weight % of sulfur (S) in the sulfur-based compound present in the positive electrode based on the total weight of sulfur (S) in the sulfur-based compound contained in the lithium-sulfur battery.

9. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery satisfies the following formula 3: [Formula 3] 10.667 × R S / C - 10.633 > R SL Wherein R SL is the content ratio of sulfur (S) according to Formula 1, and Wherein R S / C is the weight ratio of sulfur (S) to carbon (C) in the sulfur-carbon composite. 10 . The lithium-sulfur battery according to claim 1 , wherein the sulfur-carbon composite has a sulfur / carbon weight ratio (S / C weight ratio) of 2.5 g / g or less.

11. The lithium-sulfur battery according to claim 1, wherein the positive electrode comprises a current collector and a positive electrode active material layer comprising the sulfur-carbon composite, and The weight of the sulfur-carbon composite is 80 wt % or more based on the total weight of the positive electrode active material layer.

12. The lithium-sulfur battery according to claim 1, wherein a weight ratio of the electrolyte to sulfur in the sulfur-carbon composite (E1 / S weight ratio) is 3.5 g / g or less.

13. The lithium-sulfur battery according to claim 1, wherein the electrolyte comprises acyclic ether, cyclic ether or a mixture thereof.

14. The lithium-sulfur battery according to claim 13, wherein the electrolyte comprises a mixture of the non-cyclic ether and the cyclic ether, and wherein the volume ratio of the non-cyclic ether to the cyclic ether is 5:95 to 95:5 (volume / volume). 15 . The lithium-sulfur battery according to claim 1 , wherein the specific capacity of the lithium-sulfur battery is 60% or more of a theoretical specific capacity calculated from the total amount of the sulfur-based compound contained in the lithium-sulfur battery.

16. The lithium-sulfur battery according to claim 15, wherein the sulfur-based compound comprises inorganic sulfur (S8), lithium (poly)sulfide (Li2S x , 1≤x≤8) or a mixture thereof. 17 . The lithium-sulfur battery according to claim 1 , wherein the lithium-sulfur battery has a specific capacity of 1,000 mAh / g or more.

18. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery has an energy density of 300 Wh / kg or more.

19. The lithium-sulfur battery according to claim 1, wherein the lithium-sulfur battery is a coin-type battery, a pouch-type battery, or a cylindrical battery.

20. A method for evaluating the specific capacity of a lithium-sulfur battery, the lithium-sulfur battery comprising a positive electrode comprising a sulfur-carbon composite, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode or the electrolyte comprises a sulfur-based compound, the evaluation method comprising: The sulfur (S) content ratio (R SL ) is a lithium-sulfur battery with a capacity below 15% and is determined to be a high specific capacity battery: [Formula 1] R SL (%) = W SE / W SP × 100 Wherein W SE is the weight of sulfur (S) in the sulfur-based compounds present in the electrolyte, and Wherein W SP is the weight of sulfur (S) in the sulfur-based compound present in the positive electrode. 21 . The evaluation method according to claim 20 , wherein the high specific capacity battery has a specific capacity of 1,000 mAh / g or more.

Citation Information

Patent Citations

  • Curcumin complex composition and method for preparing the same

    KR1020230057999A

  • Apparatus and method for detecting operation of application

    KR1020230133558A